Frequência de células escamosas atípicas de significado indeterminado (ASCUS) em mulheres grávidas e não grávidas - Dufloth, Rozany Mucha [UNESP]; Vieira, Luiz Fernando Fonseca [UNESP]; Xavier Júnior, José Candido Caldeira [UNESP]; Vale, Diama Bhadra [UNESP]; Zeferino, Luiz Carlos [UNESP] (FapUNIFESP (SciELO), 2015)
PURPOSE: To compare the frequency of an ASCUS Pap Smear result in pregnant and non-pregnant women, stratified by age group. METHODS: We analyzed the results of 1,336,180 cytopathologyc exams of Pap smears performed between 2000 and 2009 (ten years) with the purpose of screening for cervical carcinoma. Comparisons were made between pregnant and non-pregnant women, and the sample was stratified into three age groups (20–24, 25–29 and 30–34 years). The χ2 test was used and the magnitude of association was determined by the by Odds Ratio (OR) with the 95% confidence interval (95%CI). RESULTS: A Total of 447,489 samples were excluded on the basis of the criteria adopted, for a total final sample of 37,137 pregnant women and 851,554 non-pregnant women. An ASCUS result was detected in 1.2% of cases, with a significant difference between pregnant and non-pregnant women in the age groups of 20-24 years (OR=0.85; 95%CI 0.75–0.97) and 25-29 years (OR=0.78; 95%CI 0.63–0.96). There was no difference in the group between 30–34 years (OR=0.76; 95%CI 0.57–1.03). CONCLUSIONS: This study suggested that non-pregnant women have a higher frequency of ASCUS, most evident in the age group of 20 to 29 years. The collection of cervical cancer screening should not be a compulsory part of the prenatal routine.
Frequency of atypical squamous cells of undetermined significance (ASCUS) for pregnant and non-pregnant women
Keywords: Cervical intraepithelial neoplasia/epidemiology; Health surveys; Papanicolaou test; Pregnancy